2022
DOI: 10.3329/bjas.v51i1.58884
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fresh and frozen semen of Red Chittagong Cattle

Abstract: Semen production from breeding bulls used in Artificial Insemination (AI) program is of great importance in cattle breeding. Good quality semen has positive effect on the fertility of cows and heifers. The aim of this study was to evaluate the quality and assessed as the freezing ability of Red Chittagong Cattle (RCC) bull with fresh-diluted semen and frozen semen. The parameters of semen characteristics included were volume per ejaculate (ml), percentage of mass motility, normal and abnormal sperm, and sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
2
Order By: Relevance
“…Present study observation was comparatively lower than 9.3 ml [ 51 ], 6.3 ± 0.5 ml [ 52 ] in local bull. In contrary, this observation was comparatively higher than the report of 2.58–4.01 ml in RCC [ 53 ] and 3.22 ± 0.09 ml in RCC [ 54 ] that might be due to breed differences. Accessory gland secretions also play an important role in influencing ejaculate volume [ 55 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Present study observation was comparatively lower than 9.3 ml [ 51 ], 6.3 ± 0.5 ml [ 52 ] in local bull. In contrary, this observation was comparatively higher than the report of 2.58–4.01 ml in RCC [ 53 ] and 3.22 ± 0.09 ml in RCC [ 54 ] that might be due to breed differences. Accessory gland secretions also play an important role in influencing ejaculate volume [ 55 ].…”
Section: Discussioncontrasting
confidence: 90%
“…In the current study, average sperm concentration was found 1510.27 ± 844.07 million/ml which was similar with the findings in Munshiganj bull (1669.60 ± 192.07 million/ml) [ 48 ]and (1796 ± 122.29 million/ml) [ 56 ]. The present study findings was much higher than the report of [ 54 ] (907.39 ± 23.01 million/ml in RCC bull), and (1035.24 ± 279.79 to 1088.12 ± 297.14 million/ml) in Bali bull in Indonesia [ 49 ]. Breed may be the contributing factor for this difference.…”
Section: Discussioncontrasting
confidence: 85%
“…The normal spermatozoa more than 80% was found in semen group III, more than 90% in group II and more than 95% in group I. This results was in accordance with reported by Arefin et al (2022) (Morrell et al, 2018).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 92%
“…The mass motility of spermatozoa in this study was in the average of 3 + (+++), which indicates the number of spermatozoa that were moving together very dense (densum), estimated more than 90% spermatozoa moving forward (progressive). This result followed by Arefin et al (2022), 62.11 ± 0,56% in Red Chittagong Cattle semen and Diansyah et al ( 2022), 94.94 ± 2.75%.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 69%
“…Total, progressive, static and slow motility of the fresh vs. post thawed Munshiganj semen were (84.69 ± 4.28 vs. 52.97 ± 3.13), (72.53 ± 2.91 vs. 43.71 ± 1.57), (15.31 ± 4.28 vs. 47.03 ± 3.13) and (1.23 ± 0.60 vs. 0.58 ± 0.18) respectively [29]. The average mass motility of fresh and frozen sperm in RCC bulls ranged between 55.85% -64.31% and 44.50% -53.50% respectively [35]. Fresh sperm motility of Red Chittagong bulls was 62.12 ± 0.97% [27].…”
Section: Discussionmentioning
confidence: 99%